Performance of Finnish Hedge Funds during Financial Crisis - Huhtala, Katja (My University, 2013)
Hedge funds are alternative investment vehicles which are marketed to achieve absolute returns regardless of the direction and the fluctuations of the capital markets. Hedge funds use several investment strategies in order to gain a positive return on investment in every market situation. Hedge funds use considerably leverage and derivatives in their trading, so these funds have a lot dissimilarities compared to traditional investment instruments. The purpose of this study is to investigate the performance of hedge funds registered in Finland and to measure if they are able to achieve positive absolute returns. Additionally this study examines the impact of market variables to Finnish hedge funds. The previous financial crisis began in 2008. The research period of this study is from January 2007 to December 2010 which enables to investigate if the declining markets have an effect on hedge fund performance. Finnish hedge funds risk-adjusted returns are measured with the Sharpe ratio and compared to four market indexes in order to discover whether hedge funds have outperformed the benchmarks. The relation of Finnish hedge funds returns and market returns is investigated with the regression model. The empirical research of this study gives evidence that Finnish hedge funds risk-adjusted returns have been weak during the previous financial crisis. Finnish hedge funds have not been able to outperform the market indexes. The coefficient determinations were low. Different diagnostics indicate that there was excessive correlation of variables present with the regression model of this study. Therefore the results of this model may be biased and firm conclusions cannot be reached.
Keywords: Hedge funds; performance; risk-adjusted return.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|